Effects of feeding organic acid blends on growth performance in pigs from prestarter to finisher period. - Chang, Y. K.; Loh, T. C.; Lee, C. S.; Fong, C. W.; Kok, P. C. (2009)
Organic and inorganic acid blends (OAB) are commonly used as growth enhancers due to their antibacterial effect in feed and the gastrointestinal tract. It has been reported that the nutritive effect of organic acids is most pronounced in weanling pigs, which often suffer from digestive disturbances resulting in diarrhoea related to infections with E. coli. However, information of feeding OAB in grower and finisher pigs is still very limited. Thus, a study was conducted to determine the effects of OAB on growth performance in pigs from prestarter to finisher period. A total of 160 postweaning pigs (Landrace x Large White x Duroc) were housed in 8 pens (20 pigs per pen) for creep and prestarter periods in weaner pens; whereas starter and grower period was conducted in grower and finisher units. All the pigs were allocated to the following treatments: 1. Basal diet (as control) was offered throughout the experimental period (creep, prestarter, starter and finisher), 2. basal diet + OrgacidsTM (Tcreep-finisher) was offered during creep, prestarter, starter and finisher periods. OrgacidsTM was supplemented at 2 kg per ton for creep and prestarter feed and 1 kg per ton for starter and grower feed respectively. The feed intake was measured weekly while the body weight gain for each pig was measured on day 1 and the day for changes of diets during the experimental period. Feed and drinking water was provided ad libitum and the experiment was conducted for 162 days. No significant differences (P>0.05) were found during the creep feeding period. The feed intake for Tcreep-finisher was significantly higher (P<0.05) than the control during prestarter feeding period. No significant results (P>0.05) were found for body weight, growth rate, feed intake and feed conversion ratio among the treatments during the starter feeding period. The body weight and growth rate for Tcreep-finisher was significnatly higher (P<0.05) than the control during the grower feeding period.